Complete horizontal gaze palsy due to bilateral paramedian pontine reticular formation involvement as a presentation of multiple sclerosis: a case report - Amirhossein Akhavan Sigari; Masoud Etemadifar; Mehri Salari (BMC Neurology, 2019)
Abstract Background Demyelinating central nervous system diseases include several disorders that multiple sclerosis (MS) is identified as the most common among them. Ocular movement disturbances are a typical presentation in MS patients where lesions affect the complex and interconnected pathways involved in eye motion. Centers for gaze control are located in the pons primarily; therefore, lesions involving these centers can be presented with abnormalities in gaze. However, bilateral lesions in pontine gaze centers are exceptionally rare. Case presentation A 16-year-old girl with bilateral horizontal gaze palsy was referred to the neurology clinic. Magnetic resonance imaging of the patient indicated bilateral hyperintensities in the pons at the level of the paramedian pontine reticular formation. The patient was diagnosed with multiple sclerosis with respect to clinical and imaging findings and managed. Conclusion Ocular movement abnormalities are a commonly encountered manifestation in patients with multiple sclerosis, however, bilateral gaze palsy is an exceptionally rare sign and should guide the physician to contemplate for anticipated lesions in the pons, and suspect MS, especially in childbearing-aged women. Although an extensive workup should also be done to rule out possible mimickers.